Peran Gender dalam Kegiatan Usaha Tani Buah Tomat di Kabupaten Gowa - Hasriani; Arwati, Sitti; Asih, Rahma Yuniartie; Ferdimastiar (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Gender provides a conceptual reference for social relations between men and women and the differences in function and role of both. Bontotangnga Village, Bontolempangan District, Gowa Regency, is one of the centers of large tomato producers. The division of roles based on gender is still carried out because of the influence of social and cultural aspects that are very strong in the area. This study aims to determine the division of roles and decision-making based on gender in tomato farming activities. The main sample consisted of 18 farmer households with tomato farming businesses. The sampling method was purposeful sampling. Data collection used open and direct questionnaires. The primary and secondary data obtained were then analyzed qualitatively. The role of gender in managing tomato farming in Bontotangnga Village, Bontolempangan District, Gowa Regency, is dominated by the farmer's husband in every series of farming activities. This shows gender inequality due to the imbalance in the division of roles in tomato farming activities. Gender equality has begun to be applied to decision-making in managing farming businesses. Demonstrated by openness, exchanging suggestions and opinions between husband and wife farmers.